Targeting c-Jun orchestrates heat stroke-induced myocardial injury and reveals its biomarker potential - Xiang, Yunfei; Huang, Rui; Jiang, Xuemei; Chen, Qingsong; Luo, Can; Wang, Hongxia; Jiang, Junyu; Xie, Jia; Huang, Guangbin; Liu, Menglong; Ma, Yu; Du, Dingyuan; et al. (Frontiers in Immunology, 2025)
BackgroundPatients affected by heat stroke (HS) develop myocardial injury at an early stage and exhibit a significantly higher risk of death than those without myocardial injury.MethodsWe used WGCNA and myocardial tissue transcriptome sequencing to identify candidate DEGs associated with HS-induced myocardial injury. Immune infiltration and functional enrichment analyses were performed to investigate the correlation between candidate DEGs and immune cell populations and their biological functions. Protein–protein interaction (PPI) network analysis was used to identify hub genes. Clinical validation was performed through ELISA of blood samples from patients with HS, followed by construction of a hub gene-based prognostic nomogram. Additionally, the L1000FWD platform was used to screen potential small-molecule therapeutic drugs. Finally, we established HS mice models and cellular models to validate the therapeutic efficacy and underlying mechanisms of the selected compounds.ResultsThirteen candidate DEGs were identified in the HS myocardial tissues. Immune infiltration analysis showed significant positive correlations between these DEGs and macrophages, NK cells, and dendritic cells. Functional enrichment analysis indicated that the candidate DEGs were predominantly enriched in the MAPK signaling pathway. PPI network analysis identified JUN as a key hub gene in HS-induced myocardial injury. Clinical validation showed that c-Jun levels were significantly elevated in patients with than in those without HS myocardial injury (p < 0.001) with an area under the curve (AUC) of 0.781 that indicated diagnostic accuracy. A prognostic nomogram based on c-Jun achieved an AUC of 0.906 for predicting patient outcomes. Furthermore, the L1000FWD platform identified ZG-10 as a potential therapeutic drug. In vivo and in vitro experiments showed that ZG-10 improved cardiac function in HS mouse models, alleviated c-Jun-mediated inflammatory responses and apoptosis in myocardial tissues, and inhibited the JNK/p38 MAPK pathway to downregulate c-Jun expression.ConclusionsThis study has systematically elucidated the central role of c-Jun in HS-induced myocardial injury. We have provided a novel biomarker for early diagnosis and prognostic evaluation of HS-induced myocardial injury. Additionally, we have identified ZG-10 as a potential therapeutic drug for HS-induced myocardial injury, which is a new treatment strategy for this condition.